Unusual Malignancies After Small Bowel Transplantation in Children: A European Single Centre Experience. (July 2018) - Gerlach, Undine; Morland, Bruce; Hobin, D; Solanki, G; Sharif, Khalid; Mirza, Darius; Gupte, Girish
Abstract : Background: Post transplant malignancies i.e lymphomas is a recognised complication in small bowel transplant-recipients but are mostly secondary to Epstein-Barr virus infection. There is an increased risk for malignancies in unusual sites in small bowel transplant recipients as compared to other solid organ transplants and the general population Objective: To evaluate the incidence, course and outcome of unusual malignancies in children after small bowel transplantation. Methods: Retrospective analysis of children who underwent small bowel transplantation for primary digestive disorders at Birmingham Children's Hospital between January1993 and December 2017. Results: Ninety eight small bowel transplants were performed in 90 children (49 male, 41 females) with an underlying primary digestive disorder. Median age was 2.7 years (0.6-16.2) and weight was 14.5 kg (5.7-53.2) at time of transplant. Within this cohort, we identified four cases of unusual malignancies at rare sites of presentation. One patient developed cerebral post-transplant proliferative disorder (PTLD), two patients were diagnosed with smooth muscle tumours (SMT), located at the stomal orifice and in cervicothoracic paravertebral area, respectively, and the last patient developed a retroperitoneal angiosarcoma. Unfortunately, the overall patient outcome was poor in all but one child with SMT, who currently survives with Cytotoxic T cell therapy. Conclusion: Unusual malignancies can occur in approximately 5% of children following small bowel transplantation. A high index of suspicion is required for a timely diagnosis and adequate treatment.